Improving Number Concept Recognition in 4–5 Year Old Children Through the Educational Game of Congklak at RA Al-Madinah Jakarta - Trisnanti, Nidia Rahayu; Rina Syafrida; Ine Nirmala (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study aimed to examine the effect of using congklak on the ability to understand number concepts among children aged 4–5 years at RA Al-Madinah Jakarta. The research employed an experimental method with a one-group pretest-posttest design. A total of 13 children were selected using purposive sampling based on age and cognitive readiness criteria. The research instrument was a number concept ability test covering four aspects: counting objects, rote counting, associating numbers with quantities, and comparing quantities. Data analysis involved normality and linearity tests, followed by a simple linear regression analysis. The results indicated that the data were normally distributed and the relationship between variables was linear. The regression test showed a significance value (p) = 0.006 < 0.05, indicating a significant effect of the congklak game on children's number concept understanding. The coefficient of determination (R²) was 0.515, meaning that 51.5% of the variation in the dependent variable was explained by the independent variable. These findings demonstrate that congklak is an effective learning medium that supports the enhancement of children's number concept skills in a joyful and meaningful way. Therefore, traditional games such as congklak deserve to be considered as alternative instructional media in early childhood mathematics education.